EPID-09. CMMRD (CONSTITUTIONAL MISMATCH REPAIR DEFICIENCY) ASSOCIATED-BRAIN TUMORS: REPORT FROM THE EUROPEAN C4CMMRD CONSORTIUM. Issue 2 (22nd June 2018) - Guerrini-Rousseau, Léa; Colas, Chrystelle; Wimmer, Katharina; Devalck, Christine; Opocher, Enrico; Bourdeaut, Franck; Andreiuolo, Felipe; Dahan, Karin; Genuardi, Maurizio; Goldberg, Yael; Kuhlen, Michaela; Alonso, Vanesa Pérez; et al.
Abstract: BACKGROUND: Constitutional mismatch repair deficiency (CMMRD) is a rare childhood cancer predisposition syndrome (OMIM#276300) due to biallelic germline mutations in MMR genes, leading to a broad spectrum of childhood malignancies including brain, hematologic and colorectal cancers associated with café-au-lait macules (CALM). METHODS: Malignant brain tumors (BT) were reported in 48/78 patients (10 countries), registered in the C4MMRD database. RESULTS: Overall, 55 BT (47 high-grade gliomas (HGG) and 8 embryonal tumors) were diagnosed in 48 patients between 1988-2017. Median age at the first BT was 9.1y (1.1-40.6) with 8 patients over 18y. Twenty-eight patients developed multiple malignancies (including 17 before the BT). Twenty/37 families were consanguineous. All patients had biallelic germline mutations in MMR genes: PMS2 (26pts), MSH6 (10pts), MSH2 (7pts) and MLH1 (5pts). All patients with available cutaneous data but one had CALM. In addition several patients presented developmental brain anomalies. Most patients received standard treatment before immunotherapy era, without unusual treatment-related toxicity. Median survival after the first BT was 2y. Five-year overall-survival was 23% (95%-CI, 12-41) and 45% (95%-CI, 17-76) for HGG and embryonal tumors respectively. Ten patients are alive (7 HGG and 3 medulloblastomas) at last follow-up. Among the 38 deaths, 33 patients died because of their BT (first BT=28, second BT=5) and 5 of other cancers. CONCLUSION: Despite a high risk of multiple malignancies, this series suggests that some patients may be long-term survivors. Prognosis could be improved by early recognition of this rare condition leading to more specific treatments including immunotherapy and screening for second malignancies.